1991
DOI: 10.1159/000129152
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function Derangements Induced by Portacaval Anastomosis in Normal Rats

Abstract: The purpose of this study was to determine the renal function derangements that portacaval shunting caused in previously normal rats. Eight rats suffered a surgical portacaval shunt (PCS) and another 8 a sham operation (SHAM). Renal function was investigated by determining urinary volume, sodium, potassium, creatinine and aldosterone excretion, in basal conditions and after sodium overload. Plasma renin concentration and urinary excretion of PGE2, 6-keto-PGF and TXB2 were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It has been reported that a portacaval shunt in normal rats can cause changes in renal function . Importantly, these changes were observed 30 days after the portacaval shunt was established, and the procedure did not include hepatectomy.…”
Section: Use and Limitations As Pharmacokinetic Modelsmentioning
confidence: 99%
“…It has been reported that a portacaval shunt in normal rats can cause changes in renal function . Importantly, these changes were observed 30 days after the portacaval shunt was established, and the procedure did not include hepatectomy.…”
Section: Use and Limitations As Pharmacokinetic Modelsmentioning
confidence: 99%
“…In liver diseases that result in fibrosis and portal hypertension, angiogenesis can result in the shunting of blood from the portal vein to the systemic circulation; this is referred to as portacaval anastomosis. In human liver cirrhosis, the surgical shunting of portal blood relieves backpressure and prevents further organ and vascular damage (Romeo et al 1990(Romeo et al , 1991. Among the major complications of cirrhosis and portacaval anastomosis are hyperammonemia and hepatic encephalopathy (Olde Damink et al 2002).…”
Section: Introductionmentioning
confidence: 99%